2018
DOI: 10.1177/0379572118767690
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Healthy Lifestyles School-Based Public–Private Partnerships Designed to Curb the Childhood Obesity Epidemic Globally: Lessons Learned From the Mondelēz International Foundation

Abstract: Public-private partnerships (PPPs) have been recognized as central for addressing the childhood obesity epidemic. However, very few real-world examples have been published documenting the workings of effective PPPs. The objective of this article is to identify the factors that enabled the successful implementation of school-based PPPs focusing mainly on nutrition and physical activity in 7 countries located in Asia (China and India), Africa (South Africa), Europe (Germany, United Kingdom), and Latin America (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Some initiatives use traditional intervention platforms but combine them into multicomponent, community-family-school-based childhood obesity interventions [51,52,67]. Intervention components include attendance of individual nutrition and physical activity counselling sessions for children and parents, healthy cooking workshops, and school-based extracurricular sessions of nutrition education.…”
Section: Plos Onementioning
confidence: 99%
“…Some initiatives use traditional intervention platforms but combine them into multicomponent, community-family-school-based childhood obesity interventions [51,52,67]. Intervention components include attendance of individual nutrition and physical activity counselling sessions for children and parents, healthy cooking workshops, and school-based extracurricular sessions of nutrition education.…”
Section: Plos Onementioning
confidence: 99%
“…Authorship lists were interdisciplinary in thirteen articles [ 29 , 34 , 35 , 37 , 39 , 42 49 ] and included Southern partners in sixteen articles [ 29 , 34 37 , 39 , 41 44 , 46 51 ]. Where all authors’ primary geographic affiliations could be identified ( n = 29 articles, 152 authors), 120 (79%) authors were affiliated with institutions located in the global North - Canada [ 32 , 35 , 37 , 39 , 41 , 44 , 48 , 52 ]; Europe (Switzerland, Ireland, the United Kingdom, Germany, the Netherlands) [ 30 , 31 , 38 , 40 , 45 , 50 , 53 , 54 ]; the United States [ 29 , 33 , 34 , 36 , 49 , 55 – 58 ]; Australia [ 51 ] - and 32 (21%) were located in the global South (Kenya [ 46 ], Nepal [ 47 ], Rwanda [ 43 ], and Uganda [ 42 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Thiessen et al [ 51 ], for example, justified corporate participation in a GHP by asserting that “the reason for partnering is because the private sector can achieve better efficiency through experience and innovative systems”. Problems with public-private partnerships (PPP), such as the potential for conflict-of-interest, were occasionally found [ 58 ], although without questioning the legitimacy of the PPP model. One particularly illustrative article highlights the extractive sector’s contributions to solving maternal health challenges in Papua New Guinea [ 51 ] without mentioning the same sector’s extraction of massive profits from the country and contributions to widespread environmental destruction, violence and sexual violence (c.f., [ 59 , 60 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of non-independent evaluations was high, and non-independent evaluations more frequently described success of the PPP under evaluation. For example, one paper that explicitly sought to document the effectiveness of PPPs in the area of childhood obesity was funded entirely by the Mondaléz foundation, which includes numerous chocolate and confectionary producers and which also made a payment directly to one of the senior authors for writing the paper [29]. We also classed evaluations written by individuals involved with the public partner as nonindependent under the assumption that authors who had invested time and resources in the PPP and would have interest in demonstrating the positive impact.…”
Section: Discussionmentioning
confidence: 99%